(untitled) (Environment & Health, 2023)
Introduction: Martial law continues to operate in Ukraine, in which the primary task of the state is to preserve the health and life of the population. The priority in this regard is the prevention of the harmful influence of martial law conditions on the formation of children’s bodies and the creation of conditions for their upbringing and education. Proceeding from the above, the solution to the issues regarding collective civil protection should be carried out through the construction/reconstruction of civil protection facilities, taking into account the specific conditions for both the adult population and the children’s contingent. Objective: there is the development of sanitary and hygienic requirements for civil defense structures of public and residential buildings during the period of martial law and their use in the post-war state - as dual-purpose structures, taking into account the experience of warring countries. Research methods: research methods are used in the work: bibliosemantic, analytical, hygienic and sanitary-epidemiological examination of construction projects. The materials of the research were the sanitary, urban planning and educational legislations of Ukraine and other countries in the field of designing civil defense structures of residential and public buildings, construction projects of public and residential buildings. Results: the article highlights the activities of the Laboratory, which is aimed at studying the hygienic urban planning problems of the comprehensive restoration of settlements (territories) that suffered as a result of hostilities, terrorist acts, and the development of hygienic criteria for their reconstruction in order to create safe living conditions of the population, in particular ensuring the conditions of collective civil protection in civil protection facilities of public and residential buildings. Conclusion: The activities of urban planning specialists in the direction of hygienic assessment of urban planning documentation of settlements affected by hostilities and the development of requirements for safe living of the population should be aimed at strengthening the safety determinant of public health by creating optimal conditions for collective civil protection of the population in civil protection structures of public and residential buildings - for the period of martial law and construction - the use of these structures in a dual location.